Mathventure SPLDV : Developing an Educational Math Game to Improve Students’ Critical Thinking Skills - Permatasari, Dinda Agnes; Subanti, Sri; Pramudya, Ikrar (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study aims to develop and evaluate Mathventure SPLDV, an Android-based educational game to enhance eighth-grade students’ critical thinking on Systems of Linear Equations in Two Variables. The study used the ADDIE model in a Research and Development (R&D) approach. Data were collected using questionnaires and essay tests, and analyzed using a paired samples t-test after meeting normality and homogeneity assumptions. Validation from media and material experts showed high validity (87.78% and 93.63%), while student and teacher responses showed high practicality (89.26% and 96%). A significant improvement in critical thinking was found (t = 2.638 > 1.6698), indicating H₀ rejection. Based on the results, Mathventure SPLDV is recommended for classroom use as an effective tool to support students’ critical thinking